2002
DOI: 10.1152/ajpcell.00388.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of COX-2 expression in human intestinal myofibroblasts: mechanisms of IL-1-mediated induction

Abstract: Elevated mucosal interleukin-1 (IL-1) levels are frequently seen during acute and chronic intestinal inflammation, and IL-1 neutralization lessens the severity of inflammation. One major effect of IL-1 is the increased release of eicosanoid mediators via induction of cyclooxygenase-2 (COX-2). One site of COX-2-derived prostaglandin synthesis during acute and chronic intestinal inflammation is the intestinal myofibroblast. COX-2 expression has also been documented in these cells in colonic neoplasms. Thus an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 61 publications
(74 reference statements)
7
88
0
1
Order By: Relevance
“…Furthermore, IL-1␣ enhanced TGF-␣-stimulated cell migration in a synergistic manner, mimicking the effect of PGE 2 (34). COX-2/PGE 2 signaling plays critical roles in neoangiogenesis; homozygous deletion of EP 2 R significantly reduces the number and size of intestinal polyps in APC ⌬716 mice that is associated with a reduction of VEGF expression, suggesting that PGE 2 /EP 2 signaling is critical for increased levels of VEGF in intestinal neoplasm (19 4 receptors are coupled to stimulatory G (G s ) proteins and signal through increased cAMP, whereas the EP 3 R is coupled to inhibitory G (G i ) proteins which inhibit the generation of cAMP. PGE 2 stimulates the transcription of a number of genes through the cAMP/PKA pathway where the cAMP responsive element (CRE) within the promoter plays critical roles (13,41).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, IL-1␣ enhanced TGF-␣-stimulated cell migration in a synergistic manner, mimicking the effect of PGE 2 (34). COX-2/PGE 2 signaling plays critical roles in neoangiogenesis; homozygous deletion of EP 2 R significantly reduces the number and size of intestinal polyps in APC ⌬716 mice that is associated with a reduction of VEGF expression, suggesting that PGE 2 /EP 2 signaling is critical for increased levels of VEGF in intestinal neoplasm (19 4 receptors are coupled to stimulatory G (G s ) proteins and signal through increased cAMP, whereas the EP 3 R is coupled to inhibitory G (G i ) proteins which inhibit the generation of cAMP. PGE 2 stimulates the transcription of a number of genes through the cAMP/PKA pathway where the cAMP responsive element (CRE) within the promoter plays critical roles (13,41).…”
Section: Discussionmentioning
confidence: 98%
“…The proinflammatory activities of IL-1 result largely from stimulating the expression of genes encoding inflammatory mediators. It is well-documented that IL-1 increases the expression of cyclooxygenase-2 (COX-2) 3 and the production of PGE 2 (3,4). Many biological activities of IL-1 are actually due to increased PGE 2 production (5).…”
mentioning
confidence: 99%
“…has been previously demonstrated to stabilize multiple mRNA species, such as COX-2 [42,43,[62][63][64], IL-8 [56] and NGF [65,66]. Importantly, it has already been reported that IL-1β stabilizes IL-6 mRNA in osteoblasts [16,35], fibroblasts [9], myofibroblasts [14], astrocytes [36] and fibroblast-like synoviocytes [12], although relatively little was known about the molecular mechanisms underlying this stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both can be activated by IL-1β and have been convincingly implicated in COX-2 mRNA stabilization [21,31,[41][42][43][44][45][46]. Moreover, in multiple studies, IL-1β-induced mRNA stabilization of IL-6 was shown to be crucially dependent on p38 [12,16], whereas dependence on PKC has not yet been described.…”
Section: Page 14 Of 48mentioning
confidence: 99%
“…Western blot analysis was performed as previously described (40). Briefly, cells were washed with ice-cold PBS and lysed in Laemmli sample buffer (10% glycerol, 5% 2-ME, 2% SDS, 0.002% bromphenol blue, and 62.5 mM Tris-HCl (pH 6.8)).…”
Section: Western Blot Analysismentioning
confidence: 99%